Small business in a small city: The implementation of augmented reality - Muhammad Yusuf Ariyadi; Imfrianti Augtiah; Wakhid Kurniawan (Universitas Sebelas Maret, 2024)
SMEs (Small and Medium Enterprises) are the most are the most numerous sector in Indonesia; the MSME sector is the sector that absorbs the most workers. The MSME sector will dominate in Indonesia in 2023. The MSME sector's contribution to GDP will reach 60.5%, and total labor absorption will be 96.9% (Coordinating Ministry for the Economy, 2022). The total export contribution of MSMEs increased from 14.37% in 2020 to 15.69% at the end of 2022 (Coordinating Ministry for the Economy, 2022). Technology and digitalization have touched all elements of life. Education is one of the fundamental elements in life. This research examines the implementation of technology that can synergize aspects of education, information, and, at the same time, entertainment with augmented reality (AR) screen printing media in the alternative digital business for MSMEs as an innovative media for young people in Karanganyar Regency. This research uses a qualitative approach with a 2 stage interview method: pre-test and post-test in participant testing. The participants in this research were 51 people who were classified as producers, MSME employees, and t-shirt screen printing consumers aged 15-24 years as classified by the Central Statistics Agency (Badan Pusat Statistik-BPS). To maintain good distribution, participants in this research are expected to be representatives of all sub-districts in the Karanganyar Regency area. Implementing augmented reality (AR) technology in digital business alternatives for SMEs as innovative media for young people in Karanganyar Regency has very good prospects and potential.